Association between ablation-induced baroreceptor reflex modification and procedure efficacy in patients with atrial fibrillation - Zuk, Anna; Piotrowski, Roman; Sikorska, Agnieszka; Kowalik, Ilona; Kulakowski, Piotr; Baran, Jakub (Frontiers in Cardiovascular Medicine, 2024)
Background. The autonomic nervous system (ANS) plays a significant role in atrial fibrillation (AF). Catheter ablation (CA) is a well-established treatment method for AF and significantly affects ANS, including baroreceptor (BR) function. However, little is known about the changes in the BR function caused by radiofrequency (RF) or cryoballoon energy (CB) and its impact on future AF recurrences.Purpose. To assess one-year efficacy of CA of AF in relation to BR function modification and type of ablation energy used.Methods. The study group consisted of 78 patients (25 females, mean age 58±9 years) with paroxysmal AF and first CA (39 patients in RF group and 39 in CB group). The BR function was assessed non-invasively, using tilt testing before and after CA, and three BR parameters were calculated: event count (BREC) depicting overall BR activity, slope mean depicting BR sensitivity (BRS) and BR effectiveness index (BEI). The efficacy of CA was assessed during 1-year follow-up which consisted of ambulatory visits and 24-hour Holter ECG recordings at 3, 6, and 12 months after CA. The quality of life was assessed by dedicated scale (University of Toronto Atrial Fibrillation Severity Scale (AFSS).Results. The groups did not differ in clinical or demographic data. One-year follow-up completed 35 (89.7%) patients from the CB group and 34 (87.2%) from the RF group. The efficacy of CB and RF was similar (31/35 (88.6%) versus 26/34 (76.5%), respectively). After CA, BR function decreased in both groups, with significantly greater decrease in the CB group.The changes in BR parameters were similar in responders and non-responders after CA in the whole group (BREC 10.0 (2.0-24.0) vs 12.0 (4.0-21.5), p=0.939; BRS 5.4 (3.7-6.5) vs 4.8 (3.6-7.2), p=0.809; BEI 24.8 (15.9-27.4) vs 17.5 (8.9-27.5), p=0.508, respectively). According to AFSS, the AF symptoms were significantly reduced in both groups to similar extent.CB. There is no correlation between CA-induced changes in BR parameters and ablation outcome.